Development of a biomass-fueled boiler for grain drying applications - Lapenko, H.; Gorbenko, O.; Lapenko, T.; Kolotii, S. (Scientific Progress & Innovations, 2025)
The article presents the results of research and development of an energy-efficient biomass-fired boiler designed for grain drying using locally available types of biomass as an alternative energy source. The relevance of implementing bioenergy technologies in agricultural production is substantiated, taking into account the rising cost of fossil fuels and the growing need for environmental sustainability in the agrarian sector. A comparative analysis of modern grain dryers has been conducted, highlighting their design features, advantages, and limitations in the context of biomass utilization. A boiler design has been developed, incorporating a two-section tubular recuperative heat exchanger, an automated fuel feeding system, and a multi-stage fan-driven air circulation mechanism. A distinctive feature of the proposed model is the use of high-temperature-resistant AISI 310S stainless steel in the combustion chamber, which ensures increased resistance to thermal stress, slag formation, and soot buildup. An air recirculation system for the drying chamber is also proposed to enhance the overall energy efficiency. Based on the proposed design, experimental thermal modeling was carried out. The results were generalized as temperature dependencies under various biomass feed rates. The obtained graphs and tabulated data confirm the system's predictable response to parameter changes, which is critical for automated process control and achieving high-quality grain treatment. Mathematical modeling of thermal regimes confirmed a high degree of correlation (R = 0.95) between the biomass feed rate and the temperature of air supplied to the dryer, as well as operational stability across a wide load range. The findings indicate that implementing such a boiler in agricultural practice can significantly reduce energy consumption, lower harmful emissions, and improve the autonomy of farming enterprises. The proposed technical solution offers a promising direction for modernizing grain drying equipment under current agricultural production conditions.